Classical and molecular cytogenetics of Belontia hasselti (Perciformes: Osphronemidae): Insights into the ZZ/ZW sex chromosome system - PATCHARAPORN CHAIYASAN; BOONYADA MINGKWAN; SITTHISAK JANTARAT; CHATMONGKON SUWANNAPOOM; MARCELO CIOFFI; THOMAS LIEHR; SUCHEELA TALUMPHAI; ALONGKLOD TANOMTONG; Weerayuth Supiwong (Society for Indonesian Biodiversity, 2021)
Abstract. Chaiyasan P, Mingkwan B, Jantarat S, Suwannapoom C, Cioffi MDB, Liehr T, Talumphai S, Tanomtong A, Supiwong W. 2021. Classical and molecular cytogenetics of Belontia hasselti (Perciformes: Osphronemidae): Insights into the ZZ/ZW sex chromosome system. Biodiversitas 22: 546-554. Karyotype of Java combtail fish, Belontia hasselti, from To Daeng peat swamp forest, Narathiwat Province, southern Thailand, was studied for the first time. Mitotic chromosome preparations were prepared directly from kidney cells from ten male and ten female fish. Conventional staining, NOR banding, and molecular cytogenetics with ?uorescence in situ hybridization (FISH) using 5S and 18S rDNAs, as well as microsatellites d(CA)15 and d(CAC)10 as probes were applied. The diploid chromosome number (2n) was 48 and a female heterogametic sex chromosome system (ZZ/ZW) is suggested. The fundamental numbers (NF) were 48 and 49 in males and females, respectively. The karyotype of males comprised 48 telocentric chromosomes while the female ones were composed of one metacentric and 47 telocentric chromosomes. A single Ag-NOR-bearing chromosomal pair was identified. The NOR positions were characterized at the interstitial sub-centromeric region of pair 13, which coincided with signals of 18S rDNA and d(CAC)10 probes. The 5S rDNA signals were located at interstitial sites of the largest telocentric pair. Microsatellite d(CA)15 repeats were highly distributed throughout almost all entire chromosomes except for centromeric regions on some chromosome pairs, including sex chromosomes. The present study is a novel report for a ZZ/ZW sex chromosome system of this fish family in Thailand.